Synthesis of Fe and Zn Organic Fertilizer From Palm Oil Waste - Lelita Rosanna Banjarnahor; Siti Rahmah; Marini Damanik; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2020)
Indonesia has been placed as the world's first producer of crude palm oil and crude palm oil.  In producing crude palm oil (CPO) and palm kernel oil (PKO), the palm oil industry relies heavily on processing fresh fruit bunches (FFB) at palm oil mills (POM) and is traded internationally. However, this process also produces solid organic waste [  i.e. empty bunches (EFB)], which reach up to 25 %% of FFB.  The analysis shows that the application of empty bunches as organic fertilizer has not been able to increase the amount of nutrients in palm oil leaves and increase palm oil production.  Application of palm oil mill effluent which is able to increase the amount of nutrients in palm oil, especially nitrogen and phosphate, and a positive impact to increase the production of oil palm plantations, especially on productivity (tons / ha).